Towards a Total Navigation Control System - Harris, P. A. (The International Hydrographic Review, 2015)
Most survey companies at present have navigation computer systems based around a desktop calculator. The pre-job preparation work and post-processing take place on an office-based computer. To increase production and improve the speed of producing the final report and charts, I intend to examine the requirements for an offshore computer package which will meet these needs. To many surveyors, the navigation computer is a black box that seems to absorb information, then spit out the results. To design a complex computer package, it is essential to have knowledge of the capabilities of the hardware as well as the structure of the software.